PedsCases - A Learning Module for Evaluation of Suspected Child Abuse for Medical Students - Lauren Kitney; Peter MacPherson; Peter Gill; Lionel Dibden; Melanie Lewis (Association of American Medical Colleges, 2010)
Abstract This learning module features two podcasts that review the evaluation of child abuse for medical students, as well as the common and more serious causes of abuse. These podcasts are followed by two multistep cases and six multiple-choice questions highlighting the importance of a high index of suspicion when evaluating pediatric injuries. In addition, the second case outlines a thorough algorithm for the evaluation of suspected child abuse. This module is a part of the PedsCases series, which has been integrated into the third-year undergraduate pediatric medical education curriculum at the University of Alberta. Since the focus of medical education has shifted towards independent learning, PedsCases has become a complementary educational tool and has filled a niche.